THE ECONOMICS OF REMOTE WORK AND ITS FUTURE IMPLICATIONS - Lagalur, Erappa Ramappa (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Remote work has emerged as a transformative force in modern economics, reshaping labor markets, organizational practices, and regional development. What began as a reactive shift during the COVID-19 pandemic has evolved into a sustainable model with significant implications for productivity, cost efficiency, and workforce distribution. This paper examines the multifaceted economics of remote work and projects its future impact across various dimensions, including labor, real estate, taxation, technology, and social equity. The economic appeal of remote work is driven by reduced overhead costs for employers and greater flexibility for employees. It enables access to a global talent pool, supports inclusive employment, and fosters decentralization of economic activity. Remote work has altered real estate dynamics by decreasing demand for commercial office space while increasing residential demand in non-metropolitan areas. Technological infrastructure, particularly in digital communication and cybersecurity, has become a crucial economic enabler. Additionally, this study explores emerging trends such as the rise of the digital nomad economy, remote work’s role in disaster resilience, and the restructuring of corporate innovation models. These shifts have catalyzed new economic behaviors and necessitated policy reforms in taxation, labor rights, and digital infrastructure development. However, challenges persist, including digital inequality, lack of universal social protections for gig workers, and potential negative impacts on urban economies. By evaluating the long-term implications of remote work, the study underscores the need for inclusive, forward-thinking strategies that balance flexibility with equity and efficiency. Governments, corporations, and civil society must collaborate to harness the full economic potential of remote work while addressing its limitations. As the boundaries of traditional work dissolve, remote work is poised to become a central pillar of a resilient, dynamic, and more equitable global economy.